Growth mechanism of the spherulitic propylthiouracil–kaempferol cocrystal: new perspectives into surface nucleation. Issue 12 (5th March 2021) - Xiao, Yuntian; Yang, Wenchao; Zhou, Ling; Hao, Hongxun; Bao, Ying; Yin, Qiuxiang; Xie, Chuang
Abstract : A growth mechanism of spherulitic cocrystals shows three stages of single crystal growth, non-crystallographic branching and surface nucleation. Low supersaturation forms loose spherulites, and high temperature causes "spherulites on spherulites". Abstract : As an emerging technology that can simultaneously improve the powder performance and bioavailability of drugs, spherulitic cocrystallization has increasingly shown its unique advantages. In this study, we reported a new case of a propylthiouracil/kaempferol (PTU–KA) spherulitic cocrystal and explored its growth mechanism. The morphological evolution process and growth kinetics of spherulites were studied using an in situ stereomicroscope and scanning electron microscope. The growth of the PTU–KA spherulitic cocrystal was discovered to have three stages: single crystal growth, non-crystallographic branching, and surface nucleation. It was found that increasing temperature can strengthen the surface nucleation process, and the increasing degree of supersaturation is beneficial to the formation of dense spherulites. An appropriate kinetic model has been established, which has demonstrated that the growth rate curve is not monotonical but has a maximum. Subsequent modeling analysis shows that different stages involve different control steps. Specifically, the non-crystallographic branching process is mainly dominated by interface control, while the surface nucleation process is mainly determined by diffusion control. The results of this work may provide a useful reference for the design and manufacture of spherulitic cocrystals.